Efektivitas Metode Multi Soil Layering (MSL) dalam Penurunan Total Koliform Limbah Cair Domestik - Shakira, Aisha; Mullah, Ama; Hamdan, Abd Mujahid; Lubis, Syafrina Sari (Dampak, 2023)
This research employs Multi Soil Layering (MSL), an environmentally friendly technology, to remove coliform bacteria contaminants from wastewater using a novel alternative medium. The purpose of this study is to evaluate the efficacy of the MSL method employing bio rings in reducing pollutant parameters in domestic wastewater, particularly total coliform. This study utilized Hydraulic Loading Rate (HLR) variations of 23.80 L/m2/hour, 7.14 L/m2/hour, and 3.40 L/m2/hour, as well as Hydraulic Retention Time (HRT) variations of 4, 6, 8, 10, and 12 hours. The results of domestic wastewater treatment using the MSL method using HLR variations on total coliform from 1.89  105 MPN/100mL to 6.0  102 MPN/100mL, the total colony parameter from 5.95  106 CFU/mL to 3.6  105 CFU/mL, the chemical oxygen demand parameter value of 53 mg/L with an effectiveness of 98.6%, the total suspended solid parameter is valued at 25 mg/L with reduction effectiveness of 98.6% and the pH value changes to 7.3 at the HLR variation of 3.40 L/m2/hour. As for using the HRT variation for 12 hours the total coliform from 1.16  104 MPN/100mL to 9  102 MPN/100mL, the total colony parameter from 4.91  106 CFU/mL to 3.0  105 CFU/mL, the chemical oxygen demand parameter was 92 mg/L with its effectiveness 99%, the total suspended solid parameter is 87 mg/L with reduction effectiveness of 67% and the potential of hydrogen value changes to 7.6. Therefore, the MSL method employing bio rings can be used as a new option for domestic effluent treatment. Keywords: domestic wastewater, coliform total, Multi Soil Layering (MSL)  ABSTRAK Penelitian ini menggunakan Multi Soil Layering (MSL), sebuah teknologi ramah lingkungan, untuk menghilangkan kontaminan bakteri coliform dari air limbah menggunakan media alternatif baru. Tujuan dari penelitian ini adalah untuk mengevaluasi efikasi metode MSL dengan bioring dalam menurunkan parameter polutan dalam air limbah domestik, khususnya total coliform. Penelitian ini memanfaatkan variasi Hydraulic Loading Rate (HLR) 23,80 L/m2/jam, 7,14 L/m2/jam, dan 3,40 L/m2/jam, serta variasi Hydraulic Retention Time (HRT) 4, 6, 8, 10, dan 12 jam. Hasil pengolahan air limbah domestik dengan metode MSL menggunakan variasi HLR pada total coliform dari 1,89 × 105 MPN/100mL menjadi 6,0 × 102 MPN/100 mL, parameter total koloni dari 5,95 × 106 CFU/mL menjadi 3,6 × 105 CFU/mL, nilai parameter kebutuhan oksigen kimia 53 mg/L dengan efektivitas 98,6%, parameter total padatan tersuspensi senilai 25 mg/L dengan efektivitas reduksi 98,6% dan nilai pH berubah menjadi 7,3 pada variasi HLR 3,40 L/m2/jam. Sedangkan untuk menggunakan variasi HRT selama 12 jam total coliform dari 1,16 × 104 MPN/100mL menjadi 9 × 102 MPN/100mL, parameter total koloni dari 4,91 × 106 CFU/mL menjadi 3,0 × 105 CFU/mL, kebutuhan oksigen kimia parameter 92 mg/L dengan efektivitas 99%, parameter total padatan tersuspensi 87 mg/L dengan efektivitas reduksi 67% dan nilai potensial hidrogen berubah menjadi 7,6. Oleh karena itu, metode MSL yang menggunakan bio ring dapat digunakan sebagai pilihan baru untuk pengolahan limbah rumah tangga. Kata kunci: air limbah domestik, total koliform, Multi Soil Layering (MSL)